Intersection rotational invariance regression based plant disease detection - J. Senthil; N. K. Karthikeyan; R. Senthilkumar (Plant Molecular Biology, 2026)

Surface treatment and service temperature effects on the performance of hybrid polymer composites reinforced with aluminized glass, bamboo fiber, and bagasse carbon quantum dots - S. Ramu; N. Senthilkumar; B. Deepanraj (Journal of the Indian Academy of Wood Science, 2026)

Impact of lifestyle on salivary microbiota composition and antibiotic resistance in adult periodontitis patients - Saranya S; Saveetha Priya V; Roja B; Shreejaa C; SenthilKumar N; Chellapandi P (Antonie van Leeuwenhoek, 2026)

Experimental and theoretical insights into electronic structure modulated CoMoO4/Mo2TiC2TX-MXene coupling as a dual-functional electrode for supercapattery and oxygen evolution reaction - J. Adithya Shuhruth; P. Nitesh; N. Ambikeswari; C. Sengottaiyan; Masamichi Yoshimura; B. Neppolian; Senthilkumar Ramasamy; Manikandan Kandasamy; T. Kavinkumar (Chemical Engineering Journal, 2026)

Unraveling the genetic potential of wild rice (Oryza rufipogon) for sustainable food security - Himaswetha Rajan; K. N. Ganesan; S. Manonmani; C. Gopalakrishnan; G. Senthilkumar; R. Suresh (Genetic Resources and Crop Evolution, 2025)

Unveiling the diversity of gut microbes in green lacewings (Chrysopidae: Neuroptera) and their role as protagonist in nutrition - N. Karkuzhali; Y. S. Johnson Thangaraj Edward; N. Chitra; M. Senthilkumar; J. Ramalingam (Archives of Microbiology, 2025)

Genome analysis, identification, and expression analysis of nitrogen and potassium responsive genes in cassava - Swathy Sivan; Senthilkumar K. Muthusamy; M. N. Sheela; K. Arya; B. S. Revathi; P. V. Abhilash; R. S. Neethu; A. Pooja; B. S. Prakash Krishnan (Acta Physiologiae Plantarum, 2025)

Assessing the influence of hydrogeochemical characteristics and microbial communities on monsoon dynamics in groundwater quality in north Chennai city, India - S. Syed Ahamudul Rafeek; N. Mohamed Basith; M. Mohamed Hanipha; Meera Moydeen Abdul Hameed; S. Senthilkumar (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Recent advancements in nanotechnological approaches for pollution monitoring and environmental sustainability - J. Manjunathan; M. Revathi; H. Sowmya; S. S. Meenambiga; R. Sudha; B. Prakash; Senthilkumar Nangan; Lalitha Gnanasekaran; N. Thirumalaivasan (Clean Technologies and Environmental Policy, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Recent Advances of carbon Pathways for Sustainable Environment development - K.S. Aryamol; Kuppusamy Kanagaraj; Senthilkumar Nangan; Jozef T. Haponiuk; Manunya Okhawilai; Saravanan Pandiaraj; Muhammad Bilal Hanif; Abdullah N. Alodhayb; Sabu Thomas; Natesan Thirumalaivasan; Sreeraj Gopi (Environmental Research, 2024)

Enhancing rainwater harvesting and groundwater recharge efficiency with multi-dimensional LSTM and clonal selection algorithm - N. Raghava Rao; Sree Pokkuluri Kiran; Tamboli Amena I; A. Senthilkumar; R. Sivakumar; M. Ashok Kumar; Sampathkumar Velusamy (Groundwater for Sustainable Development, 2024)

Recent advances in microbial-assisted degradation and remediation of xenobiotic contaminants; challenges and future prospects - A.K. Priya; M. Muruganandam; Anuj Kumar; N. Senthilkumar; Mohd Shkir; Bidhan Pandit; Muhammad Imran; Chander Prakash; Mohd Ubaidullah (Journal of Water Process Engineering, 2024)

Assessment of solar thermal monitoring of heat pump by using zeolite, silica gel, and alumina nanofluid - G. Antony Casmir Jayaseelan; A. Surenderpaul; T. Thandial Selvam; A. Anderson; A. Senthilkumar; Avinash Malladi; R. Venkatesh; V. N. Aneesh; R. Saravanan (Clean Technologies and Environmental Policy, 2023)

Genetic diversity analysis of Indian Cassava (Manihot esculenta Crantz) accessions using morphological and molecular markers - Swathy Sivan; Arya K; Sheela M N; Revathi B S; Prakash Krishnan B S; Senthilkumar K Muthusamy (South African Journal of Botany, 2023)

Halotolerant Nodule Rhizobial and Passenger Endophytes Alleviates Salinity Stress in Groundnut (Arachis hypogaea L.) - G. Oviya; Anandham Rangasamy; Manikandan Ariyan; R. Krishnamoorthy; M. Senthilkumar; N. O. Gopal; S. Thiyageshwari; S. Meena; S. Vincent (Journal of Plant Growth Regulation, 2023)

Enhancement of RCCI engine characteristics of Jatropha oil biodiesel as high reactivity fuel and 1-pentanol as low reactivity fuel with variable injection timing - B. Deepanraj; A. Ashok; S.K. Gugulothu; Ragireddy Venkat Reddy; N. Senthilkumar; Zafar Said; Mrinal Bhowmik (Fuel, 2023)

A critical evaluation of additive blended cashew nut shell liquid blended biodiesel performance in compression ignition engine - N. Senthilkumar; Praveen Raj; J. Ranjitha; A. Muniappan (Environment, Development and Sustainability, 2023)

A Review on Saponin Biosynthesis and its Transcriptomic Resources in Medicinal Plants - N. M. Kavya; Lateef Adil; Palanisamy Senthilkumar (Plant Molecular Biology Reporter, 2021)

Sustenance of Indian Moored Buoy Network During COVID-19 Pandemic – A Saga of Perseverance - R. Venkatesan; K. Jossia Joseph; C. Anoopa Prasad; M. Kalyani; M. Arul Muthiah; S. Ramasundaram; P. Murugesh; K. Thirumurugan; R. Sundar; B. Kesavakumar; G. Vengatesan; K. Ramesh; et al. (Frontiers in Marine Science, 2021)
The moored buoy network in the Indian Ocean revolutionized the observational programs with systematic time-series measurement of in situ data sets from remote marine locations. The real-time meteorological and oceanographic data sets significantly improved the weather forecast and warning services particularly during extreme events since its inception in 1997. The sustenance of the network requires persistent efforts to overcome the multitude of challenges such as vandalism, biofouling, rough weather, corrosion, ship time availability, and telemetry issues, among others. Besides these, the COVID-19 pandemic constrained the normal functioning of activities, mainly by delaying the maintenance of the network that resulted in losing a few expensive buoy system components and precious data sets. However, the improvements in the buoy system, in-house developed data acquisition system, and efforts in ensuring the quality of measurements together with “best practice methods” enabled 73% of the buoy network to be functional even when the cruises were reduced to 33% during the COVID-19 lockdown in 2020. The moored buoys equipped with an Indian buoy data acquisition system triggered high-frequency transmission during the Super cyclone Amphan in May 2020, which greatly helped the cyclone early warning services during the COVID-19 pandemic. The COVID-19 lockdown points toward the reliability and enhanced utility of moored buoy observations particularly when other modes of measurements are limited and necessitates more such platforms to better predict the weather systems. The present study analyzed the enhancement of the buoy program and improvisation of the buoy system that extended the life beyond the stipulated duration and enabled the high-frequency data transmission during cyclones amid the COVID-19 lockdown. The recommendations to better manage the remote platforms specifically in the event of a pandemic based on the operational experience of more than two decades were also presented.

Biostimulant activity of sulfated polysaccharide extract from red seaweed Halymenia dilatata on yield of Mung bean in greenhouse conditions - S. Vinoth; P. Gurusaravanan; M. Arun; M. Saradhadevi; N. Senthilkumar; P. Gowtham; S. R. Sivakumar (Journal of Applied Phycology, 2021)

A novel approach to preparation of nano-adsorbent from agricultural wastes (Saccharum officinarum leaves) and its environmental application - Durairaj Kaliannan; Senthilkumar Palaninaicker; Velmurugan Palanivel; Mahadik A. Mahadeo; Bulakhe N. Ravindra; Shim Jae-Jin (Environmental Science and Pollution Research, 2019)

Viral and bacterial aetiologies of epithelial ovarian cancer - S. Shanmughapriya; G. SenthilKumar; K. Vinodhini; B. C. Das; N. Vasanthi; K. Natarajaseenivasan (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Hybrid performance for yield and yield components in cardamom (Elettaria cardamom Maton) - D. Prasath; M. N. Venugopal; R. Senthilkumar; N. K. Leela (Euphytica, 2009)

Collection of plant genetic resources from Andaman and Nicobar Islands - Z. Abraham; R. Senthilkumar; K. Joseph John; T. V. R. S. Sharma; N. V. Nair; M. Unnikrishnan; P. M. Kumaran; Johnson K. George; S. Uma; M. Latha; S. S. Malik; S. K. Mishra; et al. (Genetic Resources and Crop Evolution, 2008)

Restriction Enzyme Analysis of Indian Isolates of Egg Drop Syndrome 1976 Virus Recovered from Chicken, Duck and Quail - N. Senthilkumar; J.M. Kataria; Madhuri Koti; K. Dhama; B.B. Dash (Veterinary Research Communications, 2004)

Delineation of potential zones for artificial recharge using gis - V Jothiprakash; G Marimuthu; R Muralidharan; N Senthilkumar (Journal of the Indian Society of Remote Sensing, 2003)

Polychlorinated Dibenzo- p -Dioxins, Dibenzofurans, and Dioxin-Like Polychlorinated Biphenyls in Livers of Birds from Japan - K. Senthilkumar, N. Iseki, S. Hayama, (Archives of Environmental Contamination and Toxicology, 2002)

Isolation, PCR based identification, and sensitivity pattern of environmental mycobacteria from leprosy and tuberculosis patients - D. Saravanakumar; N. Elangeswaran; S. Senthilkumar; G. Vanaja; S. Kamakshiammal; C. Chandrasekar; C. N. Deivanayagam; Manjula Sritharan; V. Sritharan (Indian Journal of Clinical Biochemistry, 2000)

Accumulation Features of Polychlorinated Biphenyls and Organochlorine Pesticides in Resident and Migratory Birds from South India - S. Tanabe; K. Senthilkumar; K. Kannan; A. N. Subramanian (Archives of Environmental Contamination and Toxicology, 1998)